Detrusor contraction duration and strength in the patients with benign prostatic enlargement - Damir Aganovic; Alden Prcic (Biomolecules & Biomedicine, 2004)
OBJECTIVE: examine detrusor contraction duration (DCD) in relation with obstruction grade and strength of detrusor contractility; analyze individual correlations of this parameter with urodynamic, physiological and symptoms variables in patients with benign prostatic enlargement (BPE).